Students with an immigrant background and active citizenship in Slovenia - Laissani, Vesna (International journal of management, knowledge and learning, 2026)
This study examines the civic attitudes of eighth-grade students in Slovenia with and without an immigrant background within the framework of civic socialization and the institutional formation of civic competences. Drawing on ICCS 2016 data, linear regression models and weighted group comparisons were employed to analyse key dimensions of active citizenship: expected political participation, gender and ethnic equality orientations, national attachment, and trust in democratic institutions.The findings indicate that several statistically significant differences exist between the groups. Students with an immigrant background report lower expectations of electoral participation and weaker national attachment. Differences also emerge in equality orientations, with lower support for gender equality but stronger endorsement of ethnic equality. No statistically significant differences were identified in trust in democratic institutions. Although some differences reached statistical significance, effect sizes remain small, suggesting limited substantive divergence between the groups.The study advances discussions on civic integration and inclusion in contexts of increasing migratory diversity and underscores the role of schools as central educational spaces for the development of active citizenship.
Keywords: active citizenship; aktivno državljanstvo; civic competences; education; ICCS 2016; immigrant background; institucionalno učenje; institutional learning; migrantsko ozadje; political participation; politična participacija; vzgoja in izobraževanje